Educação (linguística) de crianças surdas por uma intérprete de libras ouvinte : uma autoetnografia do “gretar” por entre mundos - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
These pages record my intentions, narratives, and interpretations of experiences as a teacher, sign language and Portuguese interpreter (TILSP), researcher, and author. Through the theories of Basoni (2022), Basoni and Merlo (2022), Fadini (2020), and S. Santos (2017) on the methodology of autoethnography, my record is made from my perspective and place of speech in the world. Thus, I observe the conflicts that surround the figure of the transgressive TILSP, who refuses to be neutral in the political act of education. Based on my experience with the deaf community, I problematize the pedagogical practices offered in regular schools in Goiás. The overall objective of this research is to understand how theories, power relations, linguistic dynamics, and cultural identities can intertwine, impacting the experiences of deaf students, TILSP teachers, and classroom teachers, specifically language teachers. To achieve this goal, the following specific objectives were outlined: i) to reflect on the complexities of my role as a TILSP in the context of deaf inclusion in regular, so-called "inclusive" schools, contributing to the critical linguistic education of deaf students; ii) to discuss my perceptions of pedagogical situations based on Visual Pedagogy, used by Portuguese language teachers when planning their lessons with deaf students, along with a Libras interpreter in regular education; iii) problematize the documents that attempt to prescribe the complex actions of the TILSP, observing other possibilities for implementing the school inclusion of deaf students, especially regarding the acquisition of their native language—Libras. The empirical material is selected from my logbooks, (self)observations, and my collections of written records from students over the past 16 years dedicated to deaf education. I decided to use this methodological approach because I agree with Moita Lopes's (2006) assertions that it is necessary to break with and rethink how to create and construct knowledge within a more (self)critical and (self)reflexive science—in other words, to live autoethnographically. I stitch together the pieces of this quilt with theories from Critical Applied Linguistics, Deaf Studies, and Deaf Culture, problematizing the themes of native language acquisition, critical linguistic education of Portuguese as a second language in written form, critical literacies, and citizenship development. I advocate and describe how an interpreter works through the cracks of possibility, as an act of resistance to the linguistic silencing that deaf individuals face under our mute gaze. Regarding the results obtained in the research, I highlight that implementing bilingual education for deaf students is feasible and enriching when considering the linguistic and cultural particularities of these students. I argue that by valuing Brazilian Sign Language (Libras) and integrating it into pedagogical practices, teachers can create a more inclusive and respectful school environment. Therefore, I conclude that collaboration between educators and TILSP is essential to meeting the needs of deaf students. Furthermore, activities adapted in Libras can promote linguistic and cultural diversity, combating prejudice and valuing Libras as a legitimate Brazilian language. In short, I made considerations about the contributions of autoethnographic research in my praxiologies as a teacher and TILSP, strengthening myself to continue to struggle and resist.
The (linguistic) education of deaf children by a hearing LIBRAS interpreter : an autoethnography of 'gretar' between worlds
Keywords: Educação linguística crítica; Educação de surdos; Intérprete de LIBRAS; (Trans)interculturalidade; Critical linguistic education; Deaf education; Sign language interpreter; (Trans)interculturality; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA::LINGUISTICA APLICADA